Evaluation of Sunflower Seed Oil Emulgel with Carbopol 940: Physical Properties and Moisturizing Effectiveness - Anggraeni, Wulan; Al-Hakim, Nur Achsan; Maharani, Nur Intan (Indonesian Journal of Pharmaceutical Education, 2025)
Sunflower seed oil is sourced from Helianthus annuus L., which is a plant that is extremely rich in essential fatty acids and antioxidants, so it can be used as a natural moisturizer that helps prevent, reduce, and protect skin from dryness. The purpose of this study was to evaluate the effect of variations in Carbopol 940 concentration on the physical properties and moisture effectiveness of sunflower seed oil emulgel dosage forms. The formulas were made into 3 formulas, with each concentration of Carbopol 940 for each formula, namely F1 (1%), F2 (1.5%), and F3 (2%). Furthermore, organoleptic, homogeneity, pH, viscosity and spreadability tests were carried out, as well as irritation and moisture effectiveness tests. The results of statistical analysis using one-way ANOVA showed a significant difference (P 0.05) which clarified that F1 provided an optimal increase in skin moisture (50.00%) compared to F2 (42.75%) and F3 (45.55%) and had good and stable physical properties evaluation results. In addition, increasing the concentration of Carbopol 940 in F2 and F3 can increase viscosity, but this actually affects the stability of the physical properties and moisture effectiveness of the preparation. This research concluded that F1 is the best formula and this study provides important information for the development of effective and stable skin moisturizing products, with recommendations for the use of effective concentrations of Carbopol 940 in the formulation of emulgel dosage forms.